2017
DOI: 10.1021/acsmacrolett.7b00791
|View full text |Cite
|
Sign up to set email alerts
|

Micellar RAFT/MADIX Polymerization

Abstract: We apply the RAFT/MADIX technique to the micellar copolymerization of acrylamide and 2-acrylamido-2methylpropanesulfonic acid sodium salt with a hydrophobic monomer, 4-tert-butylstyrene. The resulting polymers have wellcontrolled molecular weight distributions. In the presence of sodium dodecyl sulfate, the polymerization is better controlled by an oligo-acrylamide chain transfer agent (PAm 7 -XA1) than by Rhodixan A1. The associative character of the polymer is maintained under RAFT polymerization conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Rearranging Müller's equation for dispersity Ð as a function of conversion, p , (eq ) gives an expression for M w as a linear function of conversion (eq ) Ð=MnormalwMnormaln=1+2pp1CnormalS Mnormalw=2CnormalSM+true(11CStrue)pM …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rearranging Müller's equation for dispersity Ð as a function of conversion, p , (eq ) gives an expression for M w as a linear function of conversion (eq ) Ð=MnormalwMnormaln=1+2pp1CnormalS Mnormalw=2CnormalSM+true(11CStrue)pM …”
Section: Resultsmentioning
confidence: 99%
“…In aqueous solution, intermolecular interactions between the hydrophobic segments lead to the formation of a physically crosslinked network, with a large increase in viscosity compared with solutions of purely hydrophilic polymers of similar molecular weight . In a recent publication, we reported the first controlled radical micellar polymerization. Carrying out micellar polymerization in the presence of a xanthate reversible addition‐fragmentation chain transfer (RAFT) agent (a technique known as Macromolecular Design by Interchange of Xanthates, or MADIX) enabled us to control the molecular weight and dispersity of polyacrylamide‐based associative copolymers as well as to prepare block copolymers containing an associative segment.…”
Section: Introductionmentioning
confidence: 99%
“…Further, both more active monomers (MAM) and low active monomers (LAM) can easily be polymerized via this technique giving rise to polymeric materials with controlled distribution molecular weight and defined composition. [35][36][37][38] Additionally, the aforementioned technique has been widely employed in the polymerization acrylamido monomers leading to the synthesis of different type of materials such as: hydrogels, [39,40] thermo-responsiveness, [41,42] associative polymers, [43,44] and multiblock copolymers. [45][46][47] Recently, Díaz-Silvestre et al [48] reported the synthesis of thermo-associative water soluble multiblock copolymers polyacrylamide (PAM) and PNIPAM through RAFT polymerization using 4,4 0 -azobis-4-cyanopentanoic acid as thermal initiator.…”
Section: Introductionmentioning
confidence: 99%
“…22 Generally, these experimental attempts were performed in sandstone reservoirs under low brine concentration and regular temperature below 100 C. Several investigations were developed by different authors and reported the impact of the polymer architecture, molar composition, salt concentration, and temperature on the ability of these prepared materials to be used as rheological modifiers in the EOR process. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] In this work, an associative water-soluble terpolymer was synthesized, characterized, and evaluated at laboratory level in order to determine its performance to act as a thickening agent, that is, a potential candidate to improve the oil recovery process. Experiments were performed in the presence of heavy crude oil sample from a carbonated reservoir located in southern México.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these experimental attempts were performed in sandstone reservoirs under low brine concentration and regular temperature below 100°C. Several investigations were developed by different authors and reported the impact of the polymer architecture, molar composition, salt concentration, and temperature on the ability of these prepared materials to be used as rheological modifiers in the EOR process 23–41 …”
Section: Introductionmentioning
confidence: 99%